Enhanced skin localization of doxycycline using microparticles and hydrogel: effect of oleic acid as penetration enhancer - Aliyah Aliyah; Windy Winalda Oktaviana; Kadek Saka Dwipayanti; Arini Putri Erdiana; Rifka Nurul Utami; Andi Dian Permana (Pharmaciana, 2021)
One of the disadvantages of gel preparations is the poor ability to penetrate the skin. Herein we developed a sodium carboxymethylcellulose (NaCMC)-based gel containing microparticle of doxycycline hyclate (DOX).Â  Oleic acid (OA) was added into the gel formulation specifically to increase the penetrability of DOX microparticles. The objective of this work was to determine the effect of varying concentration of OA on the physical characteristics, penetration and retention abilities of DOX. DOX microparticles were initially prepared using PLGA as a matrix and then incorporated into a NaCMC-based gel with various OA concentrations: 0%, 2.5%, 5%, 7.5%, and 10% for F1, F2, F3, F4, and F5, respectively. The gel preparations were evaluated for their organoleptic test, homogeneity, pH measurement, viscosity, spreadability, as well as ex vivo penetration and retention abilities. The physical characteristics tests revealed a homogeneous yellow gel with a distinctive odor and pH values compatible with the pH requirements of human skin. The retention test showed the formulation retained 1236.46 Âµg of DOX in the skin. Finally, the skin retention of DOX from microparticles loaded gel was significantly higher compared to the free DOX loaded gel, indicating the microparticles can be extremely effective in retaining the DOX in the infected area.